Development of fused deposition modelling for printing of PLA and PEEK - Thng, Jeremy Zhen Yu (2019)
This final year project aims to determine how 3D Printing parameters in Fused Deposition Modelling (FDM), such as extrusion temperature and printing speed affecting the mechanical properties of the printed test specimens. The first part of the project is designing a 3D Fused Deposition Modelling printer. Test specimens will be printed using a commonly used 3D printing material called Polylactic acid, also known as PLA. I will be testing on the mechanical properties of the specimens through the Ultimate Tensile Strength test. The results of the test will then be analysed to determine the trend and identify the best combination of printing parameters to achieve maximum mechanical properties when printing with PLA through Fused Deposition Modelling. Another objective of the project is to modify the existing FDM 3D printer to be able to print another type of thermoplastic, known as Poly-ether-ether-ketone, also more commonly known as PEEK. Modifications are necessary because PEEK possesses an extremely high melting point as compared to commonly used materials like Acrylonitrile Butadiene Styrene (ABS) or Polylactic acid (PLA). I would like to find out how the printing parameters differ with PEEK and compare the results of the mechanical tests to that of the PLA.